1998
DOI: 10.1038/33408
|View full text |Cite
|
Sign up to set email alerts
|

Altered synaptic physiology and reduced susceptibility to kainate-induced seizures in GluR6-deficient mice

Abstract: L-glutamate, the neurotransmitter of the majority of excitatory synapses in the brain, acts on three classes of ionotropic receptors: NMDA (N-methyl-D-aspartate), AMPA (alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid) and kainate receptors. Little is known about the physiological role of kainate receptors because in many experimental situations it is not possible to distinguish them from AMPA receptors. Mice with disrupted kainate receptor genes enable the study of the specific role of kainate recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
449
6
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 448 publications
(477 citation statements)
references
References 25 publications
19
449
6
3
Order By: Relevance
“…It has been suggested that CA3 neurons of the hippocampus are among the most responsive neurons to KA since these neurons degenerate following local or distal KA injections (Nadler et al, 1978, Nadler et al, 1980. In support of this, a considerable amount of work has clearly demonstrated the presence of postsynaptic KARs at the mossy fiber-CA3 synapse, and GluR6-deficient mice are less susceptible to KA-induced seizures and excitotoxic neuronal death in the CA3 region of the hippocampus (Mulle et al, 1998, Fisahn et al, 2004. Furthermore, the intracerebroventricular injection of a peptide that disrupts GluR6-PSD95-MLK3 signaling can prevent kainate-induced neuronal loss in CA3 neurons (Liu et al, 2006).…”
Section: Kainate Receptors Are Involved In Excitotoxicity and Temporamentioning
confidence: 79%
See 1 more Smart Citation
“…It has been suggested that CA3 neurons of the hippocampus are among the most responsive neurons to KA since these neurons degenerate following local or distal KA injections (Nadler et al, 1978, Nadler et al, 1980. In support of this, a considerable amount of work has clearly demonstrated the presence of postsynaptic KARs at the mossy fiber-CA3 synapse, and GluR6-deficient mice are less susceptible to KA-induced seizures and excitotoxic neuronal death in the CA3 region of the hippocampus (Mulle et al, 1998, Fisahn et al, 2004. Furthermore, the intracerebroventricular injection of a peptide that disrupts GluR6-PSD95-MLK3 signaling can prevent kainate-induced neuronal loss in CA3 neurons (Liu et al, 2006).…”
Section: Kainate Receptors Are Involved In Excitotoxicity and Temporamentioning
confidence: 79%
“…CA3 pyramidal neurons of the hippocampus are particularly sensitive since these neurons degenerate following injection of kainate (Nadler et al, 1978). Other models of TLE that lead to excessive activation of mossy fibers and a sustained release of glutamate can cause similar damage to CA3 neurons (for example see (Sloviter and Damiano, 1981)), and it is clear that KARs are involved in this excitotoxicity since GluR6-deficient mice have been shown to be less susceptible to kainate-induced degeneration of these neurons (Mulle et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Kainate receptors mediate a component of synaptic transmission at mossy fiber to CA3 inputs (Castillo et al, 1997;Vignes and Collingridge, 1997) and are required for short-and long-term synaptic remodeling at hippocampal and cortical synapses (Bortolotto et al, 1999;Contractor et al, 2001;Park et al, 2006;Rodriguez-Moreno and Lerma, 1998). Kainate receptor activation contributes to developmental regulation of GABAergic transmission , to seizure generation (Ben-Ari and Cossart, 2000;Mulle et al, 1998) and epileptiform burst activity (Fisahn et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of GluK2 by antisense oligodeoxynucleotides protects against ischemic neuronal loss in the rat hippocampal CA1 region [14]. In addition, GluK2-deficient mice exhibit resistance to neuronal degeneration and seizures induced by kainate acid [19]. These studies indicate that signaling via GluK2-containing kainate receptors is an important event in the induction of neuronal toxicity.…”
Section: Discussionmentioning
confidence: 83%